Discursive Manipulation Strategies in Tinder Swindler Documentary Movie: Socio-Semiotic Perspective - Dini Anggraheni; Anandha Anandha (Universitas Sebelas Maret, 2022)
Someone's life is significantly impacted by love. Someone searches for a romantic relationship when they are in love. Romantic love can grow even without regular or in-person interactions, such as those with a stranger from a dating app. As a new form of contactless crime, telecom and internet fraud have increased in public danger as criminals target numerous unwitting victims. This study examines the Tinder Swindler documentary's lead character from a linguistic perspective. Simon, the main character, uses persuasive techniques to convince girls to like him and follow his instructions to earn money for his opulent lifestyle.Despite con artists' scientific and technological devices, language is still the main form of communication. From Halliday’s socio-semiotic perspective, this research demonstrates how criminal suspects use discourse resources to create false information and fake identities through discursive practice, earn the trust of victims, fool, deceive, and manipulate them into providing private information and money. In this study, linked discourse materials and procedures are changed to examine the dynamic process of choosing and creating identities in the social-cultural setting. This study also provides a socio-semiotic method for avoiding dating application and internet fraud.